GENDER SENSITIVITY DALAM PENGASUHAN DAN PENDIDIKAN ANAK USIA DINI - Wahyuningsih Riyadi, Nur Eka; Paputungan, Nirmala (Musawa: Journal for Gender Studies, 2025)
Gender sensitivity in early childhood care and education is crucial considering that this period is a phase of forming children's social identities and values. However, many children are still exposed to rigid gender stereotypes from an early age, both through family environments, educational institutions, and learning media. This research aims to identify the main challenges in the application of gender-sensitive approaches in early childhood and formulate solutions that can be applied by parents, teachers, and educational institutions. The approach used is qualitative descriptive based on literature studies by examining various scientific journals, reports of international organizations, and children's education policies. The results of the study show that the main challenges in the implementation of gender sensitivity include a strong patriarchal culture in parenting practices, the lack of training of PAUD teachers related to gender equality, and the use of learning media that is still gender-biased. To overcome this, a strategy is needed that includes training teachers and parents on gender perspectives, revising the PAUD curriculum to be more inclusive, providing teaching materials that reflect the diversity of gender roles, and strengthening partnerships between schools and families. By creating an environment that is free of gender bias, children can grow and develop optimally without the pressure of social norms that limit their self-expression. This article emphasizes the importance of cross-sectoral collaboration to build the foundation of gender equality from an early age.